Well-being of children affected by HIV/AIDS in Bangladesh: a cross-sectional study. Issue 4 (2nd October 2021) - Talukdar, Jhalok Ronjan; Oyewale, Tajudeen; Hasib, Enam; Alamgir, Nadia Ishrat; Uddin, M. Ziya; Mahmud, Ilias
ABSTRACT: Children affected by HIV or AIDS (CABA) are vulnerable to social consequences such as neglect, stigma, and exclusion, leading to poor child well-being. We assessed the well-being of CABA and the factors associated with it. Our sample included 288 CABA, aged 10–18 years, from four divisions of Bangladesh – Dhaka, Chittagong, Sylhet, and Khulna. The mean age of the children was 12.93 (±2.36) years. Among the children, 58% were boys, 78% were from rural areas, and 48.6% were receiving some form of HIV-sensitive social protection services from different non-governmental organizations. Around 91% of the children were continuing their education, 93% were vaccinated according to the national immunization schedule, and 13% were infected with HIV. We found that child well-being was not significantly associated with HIV-sensitive social protection services (OR: 0.88, 95% CI: 0.40–1.95), but with family wealth (OR: 5.23, 95% CI: 1.88–14.51). Therefore, we argue for HIV-sensitive social protection services that consider the economic well-being of the families of the CABA along with other well-being aspects.